2021
DOI: 10.1007/s12262-021-03209-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Resected Malignant Tumors of the Right- and Left-Sided Colon—Is There a Difference?

Abstract: Embryological, anatomical, and immunological differences between the right-sided and left-sided colons are well known, but the difference in oncological behavior of colon tumors has only recently become the main subject of studies. Published articles propose that there is a difference not only in symptoms, but also in survival. Our aim was to analyze the clinicopathological and oncological differences among our patients who had been operated for colon cancer in our department. We examined the historical data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We would also like to thank Prof. Dr. Kamer for the interest in our article "Comparison of Resected Malignant Tumors of the Right-and Left-Sided Colon-Is There a Difference?" and for taking the time to express his concerns [2].…”
Section: Dear Editormentioning
confidence: 99%
“…We would also like to thank Prof. Dr. Kamer for the interest in our article "Comparison of Resected Malignant Tumors of the Right-and Left-Sided Colon-Is There a Difference?" and for taking the time to express his concerns [2].…”
Section: Dear Editormentioning
confidence: 99%
“…
The authors compared right-sided colon cancer (RCC) and left-sided colon cancer (LCC) in their study and reported that they found significantly more mucinous adenocarcinoma histology types in right colon cancer, but, unlike the literature, there was no significant difference between the location of the tumor in the colon and overall survival [1]. The authors reported in their study that they considered rectosigmoid, ascending colon, and splenic flexure tumors as LCC, transverse colon, hepatic flexure, descending colon, and cecum tumors as RCC [1]. However, they did not report how they made this classification.
…”
mentioning
confidence: 96%